A Cooperative Internet Backup Scheme - Lillibridge, Mark; Elnikety, Sameh; Birrell, Andrew; Burrows, Michael; Isard, Michael (Proceedings of the 2003 Usenix Annual Technical Conference, 2003)
We present a novel peer-to-peer backup technique that allows computers connected to the Internet to back up their data cooperatively: Each computer has a set of partner computers, which collectively hold its backup data. In return, it holds a part of each partner’s backup data. By adding redundancy and distributing the backup data across many partners, a highly-reliable backup can be obtained in spite of the low reliability of the average Internet machine. Because our scheme requires cooperation, it is potentially vulnerable to several novel attacks involving free riding (e.g., holding a partner’s data is costly, which tempts cheating) or disruption. We defend against these attacks using a number of new methods, including the use of periodic random challenges to ensure partners continue to hold data and the use of disk-space wasting to make cheating unproﬁtable. Results from an initial prototype show that our technique is feasible and very inexpensive: it appears to be one to two orders of magnitude cheaper than existing Internet backup services.